2017
DOI: 10.1111/pan.13181
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intravenous fentanyl around the end of surgery on emergence agitation in children: Systematic review and meta‐analysis

Abstract: The current analyses indicate that fentanyl around the end of surgery reduces the incidence of emergence agitation in children undergoing general anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…This also explains why fentanyl can reduce the occurrence of postoperative agitation. [ 20 ] However, fentanyl may increase the risks of postoperative nausea and vomiting. Moreover, if respiratory depression caused by opioids is handled improperly, which will bring serious consequence.…”
Section: Discussionmentioning
confidence: 99%
“…This also explains why fentanyl can reduce the occurrence of postoperative agitation. [ 20 ] However, fentanyl may increase the risks of postoperative nausea and vomiting. Moreover, if respiratory depression caused by opioids is handled improperly, which will bring serious consequence.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systemic review supported the use of intraoperative fentanyl in the prevention of EA. 27 They showed that fentanyl use at, or 10 to 20 minutes before, the completion of surgery was effective in reducing EA. They also showed that fentanyl administered at the end of surgery increased the incidence of PONV (to 5.12-times that of the relative risk).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the administration of fentanyl at the end of surgery delays awakening. 3,8,14 Considering the turnover time in the operating room, this is a significant advantage for saving time and increasing efficiency in clinical practice, especially in ambulatory surgeries with operation times of <30 minutes. 25 Fentanyl has the undesired side effect of respiratory depression.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis suggested that the earlier administration of fentanyl reduces the incidence of PONV and also optimally controls ED. 14 In this prospective randomized controlled trial, an extension of the aforementioned meta-analysis, we aimed to investigate the effect of the timing of fentanyl administration on PONV incidence in children undergoing tonsillectomy. We hypothesized that fentanyl administration at 10 to 15 minutes before the end of surgery would reduce the incidence of PONV compared with that at the end of surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation